TRANSBOUNDARY RIVER GOVERNANCE IN THE FACE OF UNCERTAINTY: RESILIENCE THEORY AND THE COLUMBIA RIVER TREATY (Utah Environmental Law Review; Vol 30 No 2 (2010), 2010)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Fostering resilience in social-ecological systems is a choice that we, as a democratic society, can make if we desire to continue to receive the massive benefits of the ecosystems we rely on. It is not the path we are currently on as reflected in our administrative framework, our substantive natural resource law, and specifically, our management of the Columbia River. Should we choose resilience, restructuring the current system is no small task. This paper looks primarily at the administrative framework that must change from the model of massive state and federal agencies taking a command and control approach to an infusion of resources and capacity building at the local level, while retaining overlapping state, federal and international programs to provide oversight and research and to coordinate across multiple jurisdictions. Such reform will require authorization for greater flexibility in decision-making while relying on public participation and input as a large source of accountability. It will require expenditures on monitoring the effects of decisions and the flexibility to respond to the results of monitoring. In short, the recognition of the complexity in the social-ecological system, coupled with our growing realization of the complete dependence of the human race on the ability of the ecological system to serve it, requires reform of the administrative state to allow us, as a responsible society, to respond to the challenge of managing multi-jurisdictional watersheds.